2011
DOI: 10.1590/s0074-02762011000600014
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte macrophage colony-stimulating factor enhances the modulatory effect of cytokines on monocyte-derived multinucleated giant cell formation and fungicidal activity against Paracoccidioides brasiliensis

Abstract: Multinucleated giant cells (MGC) are cells present in characteristic granulomatous inflammation induced by intracellular infectious agents or foreign materials. The present study evaluated the modulatory effect of granulocyte macrophage colony-stimulating factor (GM-CSF) in association with other cytokines such as interferon-gamma (IFN-γ), tumour necrosis factor-alpha, interleukin (IL)-10 or transforming growth factor beta (TGF-β1) on the formation of MGC from human peripheral blood monocytes stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Yasui et al demonstrated that LGCs produce decreased levels of superoxide anions, which may enable M. tuberculosis to survive within granulomas ( Yasui et al, 2011 ). On the other hand, LGCs may have better fungicidal capacities than macrophages (do Nascimento et al, 2011 ; Enelow et al, 1992 ). Enelow et al demonstrated that LGCs stimulated with phorbol myristate acetate, display enhanced fungicidal capacities against C. albicans due to elevated oxidative activity ( Enelow et al, 1992 ).…”
Section: Langhans Giant Cells Phenotype Functions and Biological Acti...mentioning
confidence: 99%
“…Yasui et al demonstrated that LGCs produce decreased levels of superoxide anions, which may enable M. tuberculosis to survive within granulomas ( Yasui et al, 2011 ). On the other hand, LGCs may have better fungicidal capacities than macrophages (do Nascimento et al, 2011 ; Enelow et al, 1992 ). Enelow et al demonstrated that LGCs stimulated with phorbol myristate acetate, display enhanced fungicidal capacities against C. albicans due to elevated oxidative activity ( Enelow et al, 1992 ).…”
Section: Langhans Giant Cells Phenotype Functions and Biological Acti...mentioning
confidence: 99%
“…The role of GM-CSF, IFN-γ, TNF-α, IL-10 and TGF-β in the generation of multinucleated giant cells, that are characteristically present in granulomas was studied, stimulating human monocytes with Paracoccidioides antigen in an in vitro setting. The authors reported that foreign body-type giant cells were preferentially induced over Langhans-type and detected an important role for GM-CSF in such giant cell formation and enhancement of fungicidal activity [132].…”
Section: Lysis Within Phagocytes and Granulomasmentioning
confidence: 99%